PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, LOKASI DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN - Tommy Trio Herlambang, 14.05.51.0049; R, Alimuddin Rizal (Students' Journal of Economic and Management, 2018)
This study aims to determine the effect of product quality, service quality, location and price perceptions of customer satisfaction (Study on customer Waroeng Steak and Shake Branch Ngaliyan Semarang). The population in this study is all customers who have bought more than one product Waroeng Steak and Shake Branch Ngaliyan Semarang. Sampling using purposive sampling technique and the number of samples processed into research data as much as 100 respondents. Data were analyzed by using multiple linear regression model. Based on the results of research that has been done shows the product quality, locations and price perception have a positive and significant impact on customer satisfaction . While the service quality has no effect on customer satisfaction. Keywords : Product Quality, Service Quality, Location, Price Perception and Customer Satisfaction